A biblioteca na forma????o humana: perman??ncia e metamorfose - Pereira, Luis Carlos (2020)
This dissertation has as object of study the use of the collection of two university libraries ??? the one from the Instituto de Filosofia e Ci??ncias Humanas (IFCH) of Universidade Estadual de Campinas (UNICAMP) and the one from the Faculdade de Filosofia, Ci??ncias e Letras (FFLCH) of Universidade de S??o Paulo (USP). The main objective of the research was to verify the use of the collection starting from the perception that the professionals of the referred libraries have of their users, considering differences and affinities between the print medium and the digital medium as supports for scientific research. The research, with a qualitative approach, uses bibliographical, documentary and field sources based on the theory of ???complex thought??? by Edgar Morin. In order to achieve what was proposed, theoretical references were raised about the subject, as well as a semi-structured interview with eleven employees from both libraries. Considering the theoretical basis, the analysis and the interpretation of the collected data, it was possible to understand more widely the use of information in its different supports by a hyperconnected society. The results indicated that undergraduate students use print reading formats more than graduate students. In relation to professors, the preference for print media is directly linked to the age group ??? younger teachers have greater adherence to digital formats. Despite this data, digital readings are well regarded as complementary resources. This research, therefore, has the potential to broaden reflections regarding studies about the functionality and the role of the university library, as well as to provide a better understanding about the act of reading in its various supports.